2018
DOI: 10.1039/c7nr09692e
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming drug-resistant lung cancer by paclitaxel loaded tetrahedral DNA nanostructures

Abstract: Paclitaxel (PTX) is an effective drug against diseases such as lung cancer, ovarian cancer, and breast cancer. However, multidrug resistance limits the clinical applications of this drug. Tetrahedral DNA nanostructures (TDNs) offer great promise as a drug delivery candidate. In our study, we prepared TDNs that were subsequently loaded with PTX (PTX/TDNs). The cytotoxicity of PTX/TDNs and PTX alone on non-small cell lung cancer (NSCLC) cells (A549) and the PTX-resistant cell line (A549/T) was determined using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
138
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 50 publications
0
138
0
Order By: Relevance
“…Therefore, TDNs possess excellent structural stability, mechanical rigidity and modification versatility . Previous studies of TDNs have shown that different cells could internalize TDNs, and then TDNs exerted influence on the cells’ biological behaviours under certain conditions . For instance, TNDs could maintain the chondrocyte phenotype, promote chondrocyte proliferation and accelerate dental pulp stem cells osteo/odontogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TDNs possess excellent structural stability, mechanical rigidity and modification versatility . Previous studies of TDNs have shown that different cells could internalize TDNs, and then TDNs exerted influence on the cells’ biological behaviours under certain conditions . For instance, TNDs could maintain the chondrocyte phenotype, promote chondrocyte proliferation and accelerate dental pulp stem cells osteo/odontogenic differentiation .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DNA nanotechnology has been developed and employed in a variety of fields owing to the extensive biological functions of DNA nanostructures . Tetrahedral framework nucleic acids (tFNAs) are synthesized by four isometric single‐stranded DNAs through a simple, rapid, and reliable process, which have been identified as 3D DNA nanostructures with a stable structure and superior mechanical properties . Many biological functions can be affected after tFNAs are transported into cells, including osteogenic differentiation, nerve tissue regeneration, anti‐inflammatory, and antioxidant effects .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple analytical techniques can be applied for verification and characterization of successful TDN construction. So far, gel electrophoresis in a nondenaturing condition is the simplest procedure used to confirm designed cDNA binding by visualizing band shift 14‐20 . The dynamic light scattering technique has been widely used to determine the size and zeta‐potential of TDN 15,21‐23 and the homogeneity of the nanostructures in solution as it directly measures the hydrodynamic size in a precise nanometer range 24 .…”
Section: Design and Characterization Of Tetrahedral Dna Nanostructuresmentioning
confidence: 99%
“…Xie and coworkers investigated the effects of paclitaxel (PTX)‐loaded TDN on PTX‐resistant non‐small‐cell lung cancer cells and found that PTX‐loaded TDN can overcome drug resistance by downregulating the expression of mdr1 gene and P‐glycoprotein, resulting in reduced drug efflux from cancer cells 16 . The same group also reported the use of AS1411‐aptamer‐modified TDN to deliver the antimetabolite 5‐fluorouracil to specific breast cancer cells (Figure 3B).…”
Section: Applications As Delivery Vehicles In Cancer Therapymentioning
confidence: 99%